How to Combine High Sunk Costs of Exporting and Low Export Survival - Joakim Gullstrand; Maria Persson (Lund University, School of Economics and Management, Department of Economics, 2012)
In endeavouring to explain the empirical puzzle that the sunk costs of exporting are important, but that, at the same time, trade flows do not, on average, survive for very long, this paper explores the concepts of core and peripheral markets. First, it illustrates that if the importance of sunk costs as well as the expected future returns from exporting are different, depending on whether the export decision refers to a core or a peripheral market, it is plausible that while firms will tend to stay on the core market for a long time, they will enter and exit the peripheral market much more frequently. Second, using firm-product-destination-specific export data for all firms in the Swedish food chain for the period 1997-2007, an empirical test is carried out to ascertain whether there is support for the hypothesis that trade duration will be longer for core markets. Employing two variables that capture different aspects of the core/periphery dimension, it is found that firms will indeed tend to stay longer in their core markets, while export decisions regarding peripheral markets are much less long-term. The conclusion, therefore, is that the empirical puzzle can be explained by taking into account the fact that the trade hysteresis literature builds on data on the core market decision to export or not, and that the trade survival literature also includes data on decisions to stay in or exit peripheral markets.
Keywords: F10; F14; 330; Sunk Costs; Trade Duration; Survival; Core v. Peripheral Markets; Sweden; Firm-Level Data; Discrete-Time Hazard Models